Genetic insights into the risk of snoring on stroke and ischemic stroke: A single-variable and multivariable Mendelian randomization - He, Qiang; Ren, Li; Li, Hao; Wang, Wenjing; Tao, Chuanyuan; Ma, Lu; You, Chao (Frontiers in Neurology, 2022)
Background Multiple risk factors of stroke have been identified in previous studies; however, the causal role of snoring in the onset of stroke is less investigated. To clarify the causal association of snoring on stroke and its subtypes, this study is performed. Methods The single nucleotide polymorphisms in relation to snoring were retrieved from the UK biobank cohort with 408,317 participants. The data for stroke and its subtypes of European ancestry (67,162 cases and 453,702 controls) were obtained from the MEGASTROKE consortium. In single-variable Mendelian randomization (SVMR) and multivariable MR (MVMR) analyses, inverse variance weighting was used as the primary estimate, complemented with sensitivity analyses more robust to pleiotropy. Results Genetically predicted snoring increased the risk of stroke (odds ratio [OR] = 2.69, 95% confidence interval [CI] = 1.19–6.08, P = 0.016) and ischemic stroke (IS) (OR = 2.82, 95% CI = 1.23–6.44, P = 0.013), but not large artery stroke (LAS) (OR = 3.02, 95% CI = 0.31–29.44, P = 0.339), cardioembolic stroke (CES) (OR = 1.51, 95% CI = 0.58–3.92, P = 0.395). We provide novel genetic evidence that snoring increases the risk of stroke and IS, but not LAS, CES, and SVS. Conclusion Our findings provide novel genetic evidence that snoring increases the risk of stroke and IS, but not LAS, CES, and SVS.